On maximum signless Laplacian Estrada index of graphs with given parameters II - Ramin Nasiri; Hamid Reza Ellahi; Gholam Hossein Fath-Tabar; Ahmad Gholami (Electronic Journal of Graph Theory and Applications (EJGTA), 2018)
The signless Laplacian Estrada index of a graph G is defined as SLEE(G) = ∑ni = 1eqi where q1, q2, …, qn are the eigenvalues of the signless Laplacian matrix of G. Following the previous work in which we have identified the unique graphs with maximum signless Laplacian Estrada index with each of the given parameters, namely, number of cut edges, pendent vertices, (vertex) connectivity, and edge connectivity, in this paper we continue our characterization for two further parameters: diameter and number of cut vertices.